THE INFLUENCE OF SANCTIONS, QUALITY OF SERVICE AND SOCIALIZATION ON COMPLIANCEOFPAY TAX AND BUILDINGS IN PANTAI GEMI VILLAGE IN STABAT LANGKAT - Siregar, Oktarini Khamilah (Accounting and Business Journal, 2019)
The purpose of this study is to analyze the influence of the sanctions, the quality of service and socialization to compliance to pay taxes the earth and buildings in the Village of Pantai Gemi Stabat Langkat simultaneously and partial. The population in this study is whole the head of the family to the taxpayer of the earth and the building is located in the Village of Pantai Gemi Stabat Langkat. Sampling technique in this research is the technique of simple random sampling technique using the slovin formula so that it obtained 96 the head of the family to the taxpayer of the earth and building the sample in this study of the 2500 head family to the taxpayer of the land and building be population. Methods of data analysis in this research using the model multiple linear regression with SPSS V17. The results in this study show that simultaneous sanctions, the quality of the services and socialization have significant positive impact compliance pay land and building tax and the partial sanctions, the quality of service and socialization have significant positive compliance pay land and building tax. The results of the test the coefficient of determination (R2 ) showed that the compliance to pay the tax of land and building able to described amounted to 34.9% by the sanctions, the quality of service and socialization, while the rest amounted to 65,1% influenced by other variables that are not included in this research that awareness the taxpayer, knowledge of taxation, level of education and the income of the taxpayer.